2007
DOI: 10.1536/ihj.48.637
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Telmisartan and Spironolactone Alleviates L-NAME Exacerbated Nephrosclerosis With an Increase in PPAR-.GAMMA. and Decrease in TGF-.BETA.1

Abstract: SUMMARYTo investigate whether the receptor blockades of angiotensin II type 1 and aldosterone receptors can prevent renal tissue injury in relation to the renal tissue mRNA levels of peroxisome proliferation-activated receptors-γ (PPAR-γ) and transforming growth factor-β 1 (TGF-β 1 ) in spontaneously hypertensive rats (SHR) given N G -nitro-L-arginine methyl ester (L-NAME), which is considered a model of malignant hypertension.This study was performed in 5 groups of 17-week-old male SHR treated for 3 weeks as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In the present study, L-NAME was given to SHR as drinking water to generate malignant hypertension (Takahashi, et al, 2007). Development of a preparation that does µmol) after 2 h. In all cases, the upper 80% of BA dissolved in the solution was taken up; the uptake amount increased according to the increment of BA concentration (data not shown).…”
Section: Preparation Of Gel Beads Containing Cs-famentioning
confidence: 66%
“…In the present study, L-NAME was given to SHR as drinking water to generate malignant hypertension (Takahashi, et al, 2007). Development of a preparation that does µmol) after 2 h. In all cases, the upper 80% of BA dissolved in the solution was taken up; the uptake amount increased according to the increment of BA concentration (data not shown).…”
Section: Preparation Of Gel Beads Containing Cs-famentioning
confidence: 66%
“…Clinical (12,17) and animal (19,42) studies indicated that the ARBs telmisartan and losartan protected against the progression of aortic aneurysms. Telmisartan was reported to decrease TGF-␤ mRNA levels (43). In addition, ARBs can attenuate canonical SMAD and noncanonical extracellular signal-regulated kinase (ERK) with respect to TGF-␤ signaling (42).…”
Section: Discussionmentioning
confidence: 99%
“…Group 1 received normal saline s.c daily, group 2 received Cremophor EL and ethanol (CsA vehicle) s.c daily, group 3 received CsA 25 mg/kg/day s.c once daily (Lee et al, 1999;del Moral et al, 1997) and group 4 received telmisartan 3 mg/kg/day orally in addition to CsA (Takahashi et al, 2007).…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Signalling through the AT 1 receptor results in vasoconstriction and sodium reabsorption, and also promotes cellular growth, hypertrophy, activation of fibroblasts, and extracellular matrix deposition in the kidney (Sugiyama et al, 2005). Telmisartan exerts a variety of pleiotropic effects, including antioxidative, antiapoptotic, and anti-inflammatory effects (Sugiyama et al, 2005;Duan et al, 2009;Takahashi et al, 2007). It acts as a partial agonist of PPAR- (Benson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation